1994
DOI: 10.1042/bj2970343
|View full text |Cite
|
Sign up to set email alerts
|

Correlated expression of the 97 kDa sarcoendoplasmic reticulum Ca2+-ATPase and Rap1B in platelets and various cell lines

Abstract: Evidence has accumulated that cyclic AMP (cAMP)-induced phosphorylation of a Ras-related protein (Rap1) regulates platelet Ca2+ transport. As this transport was recently found to be controlled by two isoforms of sarcoendoplasmic reticulum Ca(2+)-ATPase (SERCA), the 100 kDa SERCA2b and the newly identified 97 kDa SERCA, we attempted to establish which isoform is involved in this regulation. For this purpose, we studied the expression and regulation of both the SERCA and Rap1 isoforms in platelets, haemopoietic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…Recognition of SERCA2b as a generic housekeeper followed evidence of universal cellular distribution, and constitutive expression during a variety of developmental and pathophysiological situations [19,20,28]. The production of SERCA2-knockout mice established that SERCA2b is essential for life, consistent with a fundamental housekeeping function [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of SERCA2b as a generic housekeeper followed evidence of universal cellular distribution, and constitutive expression during a variety of developmental and pathophysiological situations [19,20,28]. The production of SERCA2-knockout mice established that SERCA2b is essential for life, consistent with a fundamental housekeeping function [45].…”
Section: Discussionmentioning
confidence: 99%
“…The acid-stable SERCA phosphoenzyme intermediate was assayed essentially as described previously [28]. Control experiments verified that the observed $#P-phosphoenzyme bands (most intense at 90 kDa, but extending variably from 115-70 kDa) exhibited characteristic properties including : rapid turnover during a cold-ATP chase ; sensitivity to EGTA, vanadate and lanthanum ; exclusive localization in the particulate fraction (results not shown).…”
Section: Ca 2 + -Atpase and Phosphoenzyme Assaysmentioning
confidence: 99%
“…27 Interestingly, the small GTPase Rap1 which is an effector of Epac is suspected to play a role in cAMP-induced [Ca 2ϩ ] i increase via SERCA3b in megakaryocytes. 28,29 Therefore, one could imagine in cardiac myocytes, that Epac might interact with Ca 2ϩ release channels. Such hypothesis is currently undergoing investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies we have demonstrated that the KATO III gastric cancer cell line expresses the SERCA2b isoform, but not the SERCA3a protein [19][20][21]. Therefore, microsomal membranes from KATO III cells (25 µg\lane) were analysed for immunostaining by the ChS3a, ChS3b and ChS3c antibodies ( Figure 2B, lanes 1, 3 and 5, respectively).…”
Section: Antibodies Specific For the Serca3 Variants Recognize Distinmentioning
confidence: 99%
“…In human non-muscle tissues the housekeeping SERCA2b [15,16] and a SERCA3 isoform [17,18] (SERCA3a according to the recent nomenclature) have been identified. The presence of a SERCA protein recognized by PL\IM 430, a monoclonal anti-SERCA antibody raised against highly purified platelet intracellular membranes, has also been demonstrated [19,20] ; however, the identity of this SERCA form has long been debated [21][22][23]. While two alternatively spliced variants have long been known for both SERCA1 and SERCA2 [14][15][16]24,25], alternative splicing of the human SERCA3 pre-mRNA has only recently been reported by three independent groups [26][27][28].…”
Section: Introductionmentioning
confidence: 99%